FRAUD DIAMOND THEORY DAN KUALITAS PENGELOLAAN KEUANGAN DENGAN MODERASI SISTEM PENGENDALIAN INTERNAL - Evi Yuli Susanti; Gideon Setyo Budiwitjaksono (Behavioral Accounting Journal, 2019)
Regional financial management is a key element in good governance. The preparation of financial statements based on government accounting standards is a form of quality financial statement management. It can shows the performance of government that always realizes transparency and accountability of local governments. This study aims to examine the effect of fraud diamond theory on the quality of financial management with an internal control system as a moderating variable. This study uses quantitative methods and data samples of 90 employees in the Regional Apparatus Organization (Organisasi Perangkat Daerah – OPD) Malang City, East Java, with a purposive sampling technique based on criteria. Data analysis using Path Analysis techniques. The results showed that pressure, opportunity, rationalization and ability affect the quality of financial management. While the internal control system is not able to strengthen or weaken the influence of pressure, opportunity, rationalization and ability to the quality of financial management.